Drought-tolerant fungal microbes, Aspergillus oryzae and Aspergillus fumigatus, elevate physiohormonal and antioxidant responses of maize under drought stress - Niaz, Kiran; Rauf, Mamoona; Arif, Muhammad; Hamayun, Muhammad; Gul, Humaira; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Wu, Qiang-Sheng (Frontiers in Microbiology, 2024)
IntroductionTemporary and extended drought stress accelerates phytohormones and reactive oxygen species (ROS) in plants, however, the fate of the plants under stress is mostly determined by the metabolic and molecular reprogramming, which can be modulated by the application of habitat-adapted fungi that triggers resistance to stress upon symbiotic association.MethodsThe present research exhibited the exploitation of the newly isolated, drought habitat-adapted fungal endophytic consortium of SAB (Aspergillus oryzae) and CBW (Aspergillus fumigatus), on maize under drought stress. SAB and CBW primarily hosted the root tissues of Conyza bonariensis L., which have not been reported earlier, and sufficiently produced growth-promoting metabolites and antioxidants.ResultsSAB and CBW adeptly inhabited the maize roots. They promoted biomass, primary metabolites, osmolytes (protein, sugar, lipids, proline, phenolics, flavonoids), and IAA production while reducing tannins, ABA, and H2O2 contents and increasing antioxidant enzyme activities. In addition, the enhanced adventitious root development at the root/stem interface, and elongated main root development optimum stomatal activity of SAB- and CBW-inoculated maize plants were observed under drought stress. SAB and CBW modulated the expression of the ZmBSK1, ZmAPX, and ZmCAT1 genes in the maize shoot and root tissues under drought stress vs. control, signifying an essential regulatory function for SAB/CBW-induced drought stress tolerance via phytohormonal signaling pathway leading to the antioxidant upregulation.DiscussionThese findings imply that the exogenous administration of the SAB/CBW consortium might be a rather efficient strategy that contributes to optimizing the physio-hormonal attributes and antioxidant potential to alleviate the drought stress in maize.